IMPACT OF URBAN SPRAWL ON THE SPATIAL MUTATIONS OF THE CITY OF KHROUB - Assia Lifa (International Journal of Innovative Technologies in Social Science, 2024)
Algerian cities have undergone many spatial, economic, social and cultural transformations since independence, as a result of the rural exodus and the industrialization policy initiated in the 1970s. These two factors have had a significant impact on the acceleration of urban growth and expansion in all directions. Constantine is one of the most important cities suffering from urban saturation, especially as it is characterized by a narrow, hilly situation, where all its real estate assets have been consumed. It began expanding at the expense of the surrounding communes in the early 1980s, as part of the implementation of the satellite towns’ policy, which formed the "Greater Constantine assembly". The commune of El Khroub is considered the most important of these satellite towns, as it received Constantine’s surplus population under the 1974 urban development plan. El Khroub has continued to receive various housing programs over different periods, expanding at the expense of its land, including the new towns in 2000 and the urban centers in 2016, on the most fertile agricultural land, which has caused the commune to undergo spatial, property and functional transformations, particularly on the outskirts.